Analysis Of The Need For Using Mobile Games To Increase Environmental Awareness For Early Childhood - Endriyati, Endriyati; Setiawan, Abdul Haris; Sukmawati, Fatma (Universitas Sebelas Maret, 2023)
Based on their basic needs, children can recognize the natural environment (animals, plants, weather, soil, water, rocks, etc.). In addition to increasing knowledge of the natural environment, children are expected to have responsible behavior, appreciation and concern for the surrounding environment so that later they become intelligent people, have positive values and always maintain safety and cleanliness, especially in the village environment. The aims of this study were to obtain: 1) an overview of the use of mobile game media as a means of learning about the environment for early childhood students, 2) views and constraints faced by students in increasing environmental awareness, 3) learning media formulations that need attention that can developed in increasing environmental awareness. The results of the observations were in the form of an instrument for assessing the needs of Early Childhood students which were analyzed descriptively qualitatively. The researcher found that the use of learning media as a learning resource in the process of understanding environmental awareness has been carried out in the field, but has not been implemented optimally.